Rubberised fabric for fuel soft storage tanks*. (July 2018) - Rybakov, Yu.N.; Dedov, A.V.; Plokhoi, D.S.; Kolotilin, D.V.
The kinetics of extraction of dibutyl sebacinate by different grades of motor fuel from rubberised fabric based on a blend of nitrile rubbers SKN-26M and SKN-40M was investigated. The kinetics was determined according to the GOST 9.030-74 standard from the change in weight of the specimen after holding in fuel at 50°C and drying. The change in quality of the fuel after contact with the fabric was recorded from the change in the content of existent gum in fuel according to GOST 1567-97 (ISO 6246-95) and its acidity according to GOST 5985-79 before and after contact with the rubberised fabric. It was shown that the process of extraction proceeds in two stages, the time of the first of which under experimental conditions is not dependent on the type of fuel. The rate of the first stage is much higher than the rate of the second stage. The relation of rates and proportion of extracted fuel at the first and second stages depends on the type of fuel. It can be asserted that the surplus amount of extracted substances is made up of impurities, which include residual monomer or its derivatives and substances used in the synthesis of the rubber. The mechanism of extraction with extractant counterflow into the vulcanisate and its dependence on the grade of petrol is proposed, based on allowance for the diffusion processes in the system.